Towards a new point of view on the phenotype of patients with a 17q12 microdeletion syndrome. Issue 3 (16th October 2014) - Laffargue, Fanny; Bourthoumieu, Sylvie; Llanas, Brigitte; Baudouin, Véronique; Lahoche, Annie; Morin, Denis; Bessenay, Lucie; De Parscau, Loïc; Cloarec, Sylvie; Delrue, Marie-Ange; Taupiac, Emmanuelle; Dizier, Emilie; et al.
Abstract : Objective: 17q12 microdeletion syndrome involves 15 genes, including HNF1B, and is considered to confer a high risk of neuropsychiatric disorders. Patients with HNF1B gene deletion diagnosed secondary to renal disorders are only very rarely reported to have neuropsychiatric disorders. Interestingly, however, when tested, patients with HNF1B gene deletion are found to have 17q12 deletion. This brings into question the extent to which 17q12 deletion is genuinely associated with severe neuropsychological disorders and in which patients. In this study, we sought to confirm 17q12 microdeletion in kidney patients initially diagnosed with HNF1B gene deletion and evaluate neuropsychological disorders in these patients compared with those with HNF1B point mutation. Patients and design: Thirty-nine children with HNF1B disorders (26 with deletions) diagnosed secondary to renal abnormalities were included in this prospective study and tested for 17q12 microdeletion and neuropsychological disorders. Results: The same 17q12 microdeletion found in patients with neuropsychological disorders was identified in all of our patients with HNF1B deletion. Neurological examinations found no severe impairments except for one patient with autism. No significant differences were found between patients with deletions and those with point mutations as concerns learning abilities and schooling. Nevertheless, patients with deletions tended to have lower developmental quotients and more difficulties at school. Conclusions: Complete deletion of the HNF1B gene and 17q12 microdeletion syndrome are actually the same genetic disorder. The neuropsychological phenotype of patients appears less severe when 17q12 deletion is diagnosed secondary to kidney rather than neuropsychological abnormalities. These data may influence antenatal counselling.